Rancang bangun dan uji performansi mesin pencampur beberuk, makanan khas Lombok - Ansar, A.; Muttalib, S.; Sabani, R.; Kustina, R. (Universitas Mataram, 2021)
During this time the process of making beberuk was still done traditionally using a mortar as a mixer, so that production is very limited, while the market demand is quite high. To increase productivity, it is necessary to design a machine that can increase the production capacity of the beberuk. The research method begins with the mixing machine design process, then continues with the assembly process and engine performance test. The design of the mixing machine is done with two approaches namely functional approach and structural approach. Test engine performance on 3 power variations namely 144, 168, and 192 watts and 3-time variations namely 30, 45, and 60 seconds. The results showed that the cylindrical mixing chamber has a diameter of 20 cm and a height of 50 cm. The mixing tube has a rectangular hopper with dimensions of 37 cm long and 9 cm wide. Engine performance test results showed the best results on 168 watts of power treatment and 30 seconds with the results of mixing not bubbly and still looks tomato chunks and is not too smooth according to the standard beberuk food.